Regional pancreatoduodenectomy versus standard pancreatoduodenectomy with portal vein resection for pancreatic ductal adenocarcinoma with portal vein invasion. Issue 3 (19th March 2020) - Oba, A.; Ito, H.; Ono, Y.; Sato, T.; Mise, Y.; Inoue, Y.; Takahashi, Y.; Saiura, A.
Abstract : Background: Pancreatoduodenectomy (PD) with portal vein resection (PVR) is a standard operation for pancreatic ductal adenocarcinoma (PDAC) with portal vein (PV) invasion, but positive margin rates remain high. It was hypothesized that regional pancreatoduodenectomy (RPD), in which soft tissue around the PV is resected en bloc, could enhance oncological clearance and survival. Methods: This retrospective study included consecutive patients who underwent PD with PVR between January 2005 and December 2016 in a single high‐volume centre. In standard PD (SPD) with PVR, the PV was skeletonized and the surrounding soft tissue dissected. In RPD, the retropancreatic segment of the PV was resected en bloc with its surrounding soft tissue. The extent of lymphadenectomy was similar between the procedures. Results: A total of 268 patients were included (177 SPD, 91 RPD). Tumours were more often resectable in patients undergoing SPD (60·5 per cent versus 38 per cent in those having RPD; P = 0·014), and consequently they received neoadjuvant therapy less often (7·9 versus 25 per cent respectively; P < 0·001). R0 resection was achieved in 73 patients (80 per cent) in the RPD group, compared with 117 (66·1 per cent) of those in the SPD group ( P = 0·016), although perioperative outcomes were comparable between the groups. Median recurrence‐free (RFS) and overall (OS) survival were 17 and 32 months respectively in patients who had RPD, compared with 11 and 21 months in those who had SPD (RFS: P = 0·003; OS: P = 0·004). Conclusion: RPD is as safe and feasible as SPD, and may increase the survival of patients with PDAC with PV invasion. Abstract : A regional pancreatoduodenectomy (RPD) procedure was employed to enhance oncological clearance around the mesenteric vein in patients with locally advanced pancreatic cancer. This provided better local control with longer overall survival than a standard pancreatoduodenectomy procedure. Regional pancreatectomy associated with increased R0‐rate and survival Abstract : Antecedentes: La duodenopancreatectomía ( pancreaticoduodenectomy, PD) con resección de la vena porta ( portal vein resection, PVR) es una operación estándar para el adenocarcinoma ductal pancreático ( pancreatic ductal adenocarcinoma, PDAC) con invasión de la vena porta ( portal vein, PV); sin embargo, las tasas de margen positivo siguen siendo altas. Nuestra hipótesis fue que la duodenopancreatectomía regional ( regional pancreaticoduodenectomy, RPD) en la que el tejido blando alrededor de la PV se reseca en bloque podría mejorar el resultado oncológico y la supervivencia. Métodos: Este estudio retrospectivo incluyó pacientes consecutivos que se sometieron a PD con PVR entre enero de 2005 y diciembre de 2016 en un solo centro de alto volumen. En la PD estándar (SPD) con PVR, la PV se esqueletizó disecando el tejido blando circundante. En la RPD, el segmento retropancreático de la PV se resecó en bloque con el tejido blando circundante. La extensión de la linfadenectomía fue similar en ambos procedimientos. Resultados: Se incluyeron un total de 268 pacientes (177 sometidos a SPD y 91 a RPD). Los pacientes sometidos a SPD presentaron con mayor frecuencia tumores resecables (35 (38%) versus 107 (61%), P = 0, 014)) y recibieron con mayor frecuencia terapia neoadyuvante (23 (25%) versus 14 (8%), P < 0, 001)) que los pacientes sometidos a RPD. La resección R0 se logró en 73 (80%) pacientes pertenecientes al grupo RPD, en comparación con 117 (66%) pacientes sometidos a SPD ( P = 0.011), aunque los resultados perioperatorios fueron comparables entre los grupos. La mediana de supervivencia libre de recidiva ( recurrence‐free survival, RFS) y de supervivencia global ( overall survival, OS) fueron 17 meses y 31 meses, respectivamente, en pacientes sometidos a RPD, en comparación con 11 meses y 21 meses en pacientes sometidos a SPD, ( P = 0, 003 para RFS y P = 0, 004 para la OS). Conclusión: La RPD es tan segura y factible como la SPD y puede aumentar la supervivencia de pacientes con PDAC con invasión de la PV.